Post-Partum Diastasis of the Pubic Symphysis: Report of a Rare Case - Jeevitha Kamakoti Jayaraman; Prabha Ganapathy; Nalliannan Indira (Journal of Clinical and Diagnostic Research, 2015)
Post-partum pubic symphysis diastasis refers to an abnormally wide gap between the two pubic bones following delivery. It is an uncommon and under diagnosed condition resulting in acute pelvic pain. A case of pelvic diastasis in a 24-year-old G2 A1 following normal vaginal delivery is reported. Management consisted of simple conservative treatment with binders and analgesics, which were sufficient in achieving a complete reversal of the condition. The low incidence of 1 in 3700 normal vaginal deliveries over a 5 year period at Public Health Centre, Chennai, coupled with the rarity of the condition renders it as a salient presentation in the practice of our profession.